Knowledge and Perceptions about Diagnosis, Clinical Management, and Prevention of Dengue Fever among Physicians during the 2023 Outbreak: A Cross-Sectional Study in Peru - Araoz-Salinas, Julieta M. (2024)
The objective of this study was to evaluate the knowledge level and perception of dengue fever management among Peruvian physicians and to determine the factors associated with higher knowledge.We conducted an analytical cross-sectional study based on an online survey. To evaluate the factors associated with a high level of knowledge ($70% of correct answers), we used crude (cPR) and adjusted (aPR) prevalence ratios by the Poisson regression model. Of 359 respondents (median age: 33 years; male: 56.5%), 78.8% achieved a high level of knowledge. Multivariable analysis showed an independent association with having read the Peruvian clinical practice guidelines for dengue management (aPR: 1.29; 95% CI: 1.12–1.49), having experience in treating patients (aPR: 1.32; 95% CI: 1.03–1.68), and having treated cases frequently (aPR: 1.22; 95% CI: 1.02–1.46). Residing in the eastern macroregion (aPR: 0.83; 95% CI: 0.71–0.97) was associated with a low level of knowledge. In conclusion, Peruvian physicians had a high level of knowledge about dengue fever. This was associated with having clinical experience in dengue management. However, given the low level of knowledge in the eastern macroregion, educational campaigns are necessary in this area.